Penerjemahan komunikatif lagu Arab Kalam Eineh yang dipopulerkan oleh Sherine Abdel Wahab - Fatimah, Erma Nur (Maliki Interdisciplinary Journal, 2024)
This article deals with the communicative translation of the lyrics of Sherine Abdel Wahab's Arabic song Kalam Eineh. The analysis of the meaning of the song lyrics, the discovery of translation methods, the assessment of emotional correlation, and the enhancement of cultural understanding are the objectives of this study. This research is qualitative-descriptive in nature. In this study, the data collection methods were viewing and writing. The researcher listened to and read the text of the song Kalam Eineh. Once the results are collected, conclusions can be made. The results show that cultural differences, nuances, and language structures make translating Arabic songs a unique challenge. However, the translator managed to convey the meaning of the song to the target audience by using an appropriate communicative approach. The results show that a literal translation of Kalam Eineh song lyrics cannot convey the overall meaning and message of the song.